Perilaku Beragama Mahasiswa UIN Sunan Kalijaga (Studi Mahasiswa S1 Angkatan 2018 Jurusan Pendidikan Biologi Fakultas Sains dan Teknologi) - Ratnasari, Ratnasari (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
This research focused on the religious behavior of science and biology education students at the State Islamic University (UIN) Sunan Kalijaga. To answer this, Max Weber's theory was used through affective action. The purpose of this study was to determine the description of the religious behavior of biology education students at the State Islamic University (UIN) Sunan Kalijaga. This research was expected to make a new contribution to all students in general, and in particular to the State Islamic University (UIN) Sunan Kalijaga as a place used by researchers in conducting research. This type of research was a qualitative descriptive form of phenomena that occurred in the field, the research sample was 50 people from 261 populations. The sampling technique was purposive sampling, the sampling technique was based on the existence of certain objectives with consideration. The data obtained through this study were observation, interviews, and documentation which were then analyzed by data reduction, data presentation and verification. Based on the results of the study, found answers, that some biology education students have religious behavior with a fairly good category, this can be seen from their attitudes namely faith and preaching, good morals, attitudes toward religious activities, attitudes of responsibility and positive dependence, al- The Qur'an raises human consciousness, despicable moods and behavior. In addition there are driving factors in religion, namely family education, institutional education and community education.